Homozygous BUB1B mutation and susceptibility to gastrointestinal neoplasia. - Rio Frio, T; Lavoie, J; Hamel, N; Geyer, F; Kushner, Y; Novak, D; Wark, L; Capelli, C; Reis-Filho, J; Mai, S; Pastinen, T; Tischkowitz, MD; et al. (2010)
A patient received a diagnosis of adenocarcinoma of the ampulla of Vater at 34 years of age. Two decades later, adenomatous polyps were found, followed by multiple primary invasive adenocarcinomas of both the colon and the stomach. Premature chromatid separation and mosaic variegated aneuploidy, combined with structural chromosomal abnormalities, were detected in his cells. We identified a germline homozygous intronic mutation, c.2386-11A→G, in the spindle-assembly checkpoint gene BUB1B, which creates a de novo splice site that is favored over the authentic (i.e., preferentially used) site. Our findings expand the phenotype associated with BUB1B mutations and the mosaic variegated aneuploidy syndrome to include common adult-onset cancers and provide evidence for the interdependency of the APC protein (encoded by the adenomatous polyposis coli gene) and the BUBR1 protein (encoded by BUB1B) in humans. (Funded by the Turner Family Cancer Research Fund and others.).